2006
DOI: 10.1016/j.triboint.2005.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Friction and wear during twin-disc experiments under ambient and cryogenic conditions

Abstract: To cite this version:Luc Chevalier, S. Cloupet, M. Quillien. Friction and wear during twin-disc experiments under ambient and cryogenic conditions. Tribology International, Elsevier, 2006, 39 (11) proposed by Kalker (Fastsim) is used to identify the dynamic friction coefficient between these discs and to study the apparatus parameters influence on dissipated energy. Wear evolution is simulated using classical Archard's law and compared to measured profiles.Influence of ambient conditions is highlighted by comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Cryo-tribological system consists of cryogenic temperature technology and the demands of the environmental medium. In Chevalier et al., 14 the friction at the supercool condition was found to be less than the friction in the ambient condition, but the results were not stable. Cryo-temperature changes the elastic parameters and durability affecting the mechanical properties of the material.…”
Section: Introductionmentioning
confidence: 84%
“…Cryo-tribological system consists of cryogenic temperature technology and the demands of the environmental medium. In Chevalier et al., 14 the friction at the supercool condition was found to be less than the friction in the ambient condition, but the results were not stable. Cryo-temperature changes the elastic parameters and durability affecting the mechanical properties of the material.…”
Section: Introductionmentioning
confidence: 84%
“…They also found that some hard and superhard diamond-like carbon (DLC) coating gave higher friction coefficient in low temperature. In another work reported by Chevalier et al [18], the friction of steel against steel at the supercool condition was found to be less than the friction in the ambient condition, but the results were not stable.…”
Section: Introductionmentioning
confidence: 84%
“…The test was carried out on a twin-disc tribometer (SUPMECA School, Saint-Ouen, France) [51,52]. Each disk is mounted on an independent spindle driven at a maximum speed of 10,500 rpm.…”
Section: The Bench Testmentioning
confidence: 99%